A hybrid dye-clay nano-pigment: Synthesis, characterization and application in organic coatings. (December 2017) - Mahmoodi, A.; Ebrahimi, M.; Khosravi, A.; Eivaz Mohammadloo, H.
Abstract: The major objective of this study was to synthesis a hybrid dye-clay nano-pigment (DCNP) through cationic exchange reaction of methylene blue (i.e. MB) and Cloisite 15A (i.e. C15A) and its application in an epoxy coating. In fact, we wanted to prepare a high-performance blue pigment with both cationic dye and nano-clay features. The prepared hybrid pigment was incorporated in an epoxy formulation and its physical and chemical (i.e. corrosion resistance) properties were compared with the same epoxy formulation which had a conventional organic pigment (namely, C.I. pigment blue 15:2). Synthesized hybrid pigment and prepared epoxy coatings were characterized by using different techniques including CHNS, TGA, XRD, TEM, QUV accelerated weathering tester, spectrophotometry, pull-off adhesion, electrochemical impedance spectroscopy (EIS) and salt spray. Results showed that cationic exchange reaction between MB and C15A significantly improved the thermal stability of MB. DCNP represented better dispersion and more intercalated/exfoliated structure in epoxy coating in comparison with that of C15A. The color characteristics (i.e. weather stability, tinting strength and hiding power) of DCNP were found to be better than those of the conventional organic pigment. Finally, the best corrosion protection performance was observed when DCNP was incorporated into the coating formulation. Graphical abstract: Highlights: A blue hybrid nano-pigment was synthesized via a cation exchange reaction between methylene blue and Cloisite 15A. The thermal and weather stability of methylene blue improved by its cation exchange with Cloisite 15A. The color characteristics of DCNP were found to be much better than methylene blue and a conventional organic pigment. Epoxy coating containing DCNP showed better dispersion and corrosion resistance compared to other coatings.